Peran Kompensasi Dan Penilaian Kinerja Dalam Meningkatkan Kepuasan Dan Produktivitas Tenaga Kesehatan Pada Era Digitalisasi Rumah Sakit - Dewi Hastuti, Ade; Endah Puspaningrum, Florentina; Mulyadi, Edi (Plexi Digital Indonesia, 2025)
This systematic review examines how compensation and performance appraisal influence health-care workers’ job satisfaction and productivity within digital hospital settings. Following PRISMA 2020, we searched major databases (2019–2025), deduplicated records, and applied dual-review screening; twenty-five studies met the inclusion criteria. Data were extracted with a structured form; study quality was appraised using RoB2/ROBINS-I/AXIS/AMSTAR-2, and certainty of evidence was summarized with GRADE. The synthesis indicates a consistent positive association between compensation salary/benefits, bonuses, and pay-for-performance and job satisfaction, and in several contexts with productivity and retention; however, P4P effects vary by indicator design and governance capacity. Well-designed performance appraisal clear goals, measurable indicators, specific feedback, and procedural fairness is linked to higher satisfaction, engagement, and work outcomes. Digitalization acts as a moderator: EHR usability, EHR engagement programs, telemedicine integration, and digital-hospital initiatives can amplify or dampen HR policies’ effects via documentation burden and workflow changes. Certainty is generally moderate for satisfaction, and low-to-moderate for productivity, retention, and engagement. Managerial implications call for a bundled HR–digital approach aligning transparent, performance-linked compensation and developmental appraisal with measurable workflow improvements. Regulatory implications include enforcing interoperability/usability standards and valid incentive indicators. Main limitations are the predominance of observational designs, heterogeneous productivity measures, and uneven reporting of digital components. Future research should employ longitudinal or quasi-experimental designs with standardized outcomes and objective data.